Effect of housing systems on fatty acid structures of liver, abdominal fat and breast muscle in broiler production - SIMSEK, ULKU GULCIHAN; YILMAZ, OKKES; GOKCE, ZEHRA; CIFTCI, MEHMET; ERISIR, ZEKI (The Indian Journal of Animal Sciences, 2017)
This study was conducted to determine fatty acid structures of liver, abdominal fat and breast muscle (Musculus pectoralis profundus) in broiler reared in cage (CH) and floor (FH) housing systems. For this purpose, 15 broilers (Ross-308) per replicate having stable live weight were selected in each system and fatty acids analyses were simultaneously taken in summer, autumn and winter seasons by a gas chromatography (GC) system. It was found that the poultry meat had higher ratio of polyunsaturated fatty acids (PUFA), especially omega-6 fatty acids (n-6) related with the diet consumed by chicken. Cage housing sytem caused accumulation of myristic (C14: 0), palmitic (C16: 0), stearic (C18: 0), arachidic (C20: 0) and heneicosanoic (C21: 0) fatty acids in the chicken that significantly raised total saturated fatty acid (SFA) ratios of abdominal fat and pectoral muscle tissues. Proportions of total monounsaturated fatty acid (MUFA), total PUFA and PUFA/SFA of abdominal fat tissue were found higher in FH system. Proportions of omega-3 fatty acids (n-3), n-6, n-6/n-3 and PUFA/SFA were similar between groups in liver and muscle tissues. Consequently, cage housing system used by broiler production was inclined to synthesis of saturated fatty acids, especially in fat and breast muscle tissues, and changed fatty acid structure of chicken meat.